Step-by-step watercolour painting : a complete guide to mastering techniques with the Alexander brothers / Gregory and Matthew Alexander. - Alexander, Gregory, 1960- (Phoenix Illustrated, 1997)
This tutorial begins with advice on choosing materials and simple brushstrokes, followed by detailed start-to-finish projects on landscape, still life, figure and portrait painting. Each project includes problem-solving tips.